Studi Komparatif Filsafat Pendidikan Islam dan Barat - Muhammad Arif Syihabuddin (JP : JURNAL PENDIDIKAN, 2017)
The science’s development along with it alteration have created various characteristics. This condition tends to spur human on thinking up about the righteousness value. In case of viewpoint’s dissimilarity on interpreting the righteousness, there is no agreement reached yet concerning to the definition of Educational Philosophy. This varied definition, at least, could be influenced by many aspects. Philosophy’s role in the world of education was to contribute referee framework at educational philosophy’s field in order to consummate the expected educational aspiration. The discussion of Islamic Educational Philosophy could not be separated from grooved and patterned thought which developed by its thinker. As long as this era, Islamic Educational Philosophy’s thought was categorized into two main circles, cohort of critical philosophy on education or cohort (madhhab) of progressively thought and cohort (madhhab) of traditionally thought. Functionally, Islamic Educational Philosophy is a radical thought which emphasizing and directing to an Islamic Educational process. Whereas in West Education, science was not born from life viewpoint of certain religion and claimed as something with exempt value (without or no longer having value). But in truth, it’s not really exempt value, it just exempt from Religious and Godliness values. Either science was not born from life viewpoint of certain religion, because of the problematical relation between religion and science in the West.Keywords; Philosophy, Education, Islamic, West